Modified halloysite nanotubes as carrier for antimicrobials agent in wound healing materials - Abuhamed, Nader M.I
Plastic waste has become a significant issue globally, especially in the medical field, where most of the products are petroleum-based plastics. In this research, polysaccharide base films were utilized to overcome this issue. Polysaccharide materials such as thermoplastic sago starch (TPSS) promote wound healing; however, an infection is more likely to occur. Halloysite nanotubes (HNTs) are a biocompatible material that is used in medical applications. In this research, halloysite was modified by dispersing it with chloramphenicol solution. Chloramphenicol was loaded into halloysites using a magnetic stirrer. Thermoplastic sago starch (TPSS)/modified halloysite (MHNTs) biocomposite films were developed using the solution casting method. In addition, starch/ halloysite biocomposites films also were produced for comparison. Surface morphology characterization was done for the halloysite nanotubes, where it showed agglomerations of the modified halloysite. The scanning electron microscopy (SEM) images showed a good dispersion of the natural halloysite in the polymer matrix compared to the modified halloysite. Besides, modified halloysite shows higher agglomeration with further addition. X-ray diffraction spectra of the starch films showed an alteration with the addition of halloysite nanotubes, indicating intercalation of halloysites in the TPSS matrix. FTIR peaks of TPSS also showed changes with the addition of halloysite. The tensile properties demonstrated the mechanical properties of the halloysite/ thermoplastic sago starch. HNT and MHNT at 0.25 wt.% had slightly improved the tensile strength of the TPSS from 3.69 MPa to 4.11 and 3.76 MPa, respectively. However, the tensile strain was reduced when halloysite was introduced to the polymer matrix. The water absorption was decreased from 72.96% to 58.62% at 0.25 and 1 wt.% of HNT. Meanwhile, MHNT reduced the water absorption rate from 72.96% and 53.13% at 0.25 and 1 wt.% of MHNT, respectively. This reduction is attributed to its encapsulation of the chloramphenicol antibiotics which is a highly hydrophobic substance. Halloysite in nature is not an antimicrobial agent, and this was observed from the disc diffusion method. However, when HNT was modified using an antimicrobial substance, it successfully showed good susceptibility to bacterial culture. This indicates the ability of MHNTs to be used as an antibacterial carrier for wound dressing materials. The soil burial method was used to evaluate the biodegradability of TPSS biocomposites. MHNT has significantly reduced the biodegradability of TPSS compared to pure HNT. This leads to the fact that MHNT had good antimicrobial properties, which lead to the MHNT/TPSS to withstand the degradation from microbes in the soil. Results showed that halloysite could be a potential carrier for antibacterial agents. The thermoplastic sago starch can be an effective composite when incorporating with modified halloysite to withstand bacterial attacks. This research opens new doors for halloysite nanotubes to be further studied for carrying antibacterial substances or other drugs.